MENINGKATKAN KETERAMPILAN SOSIAL MENGGUNAKAN MODEL INSPIRED DAN MEDIA EDUCAPLAY SDN MELAYU 5 - Amalia Yasmiyanah, Kharisa; Ayu Pratiwi, Diani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem of this research is the low social skills of students. The low social skills of students are caused by the lack of good relationships from educators and students during learning activities. Efforts that can be made are educators using the INSPIRED learning model (PBL. TPS, NHT) and Educaplay media. This study aims to analyze the social skills of students. This research used Classroom Action Research (CAR) which mas conducted in 4 meetings. The subjects of this study ware grade IV students of SDN Melayu 5 Banjarmasin City, totaling 17 people in semester II of the 2023/2024 academic year. In this study, the data taken is qualitative data through observation of student’s social skills. The findings of this study indicate that social skills at meetings I to IV have increased from a percentage of 29% to 94% with the criteria “Very Skilled”. Based on these findings, it can be concluded that the INSPIRED model and Educaplay media can improve students’ social skills.